2019
DOI: 10.3389/fmars.2019.00481
|View full text |Cite
|
Sign up to set email alerts
|

Non-conservative Behavior of Dissolved Organic Matter and Trace Metals (Mn, Fe, Ba) Driven by Porewater Exchange in a Subtropical Mangrove-Estuary

Abstract: Estuaries play a key role in controlling the land-ocean fluxes of dissolved organic matter (DOM), nutrients and trace metals. Here, we study how mangrove-fringed areas affect the molecular DOM and trace metal composition in a subtropical estuary. We combined molecular analysis of solid-phase extractable (SPE) DOM using ultrahigh-resolution mass spectrometry with organic and inorganic bulk parameter analyses in surface and porewater along the estuarine gradient of a mangrove-fringed estuary in Australia (Coffs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 102 publications
2
14
0
Order By: Relevance
“…There was some evidence for an outer-estuary increase in P SPE-amb , Zn SPE-amb , and Ni SPE-amb at salinities between 15 and 30. Concentrations of S SPE-amb and P SPE-amb offshore from the mangrove forests were similar to those observed in the riverine endmember, while A 254SPE-amb , Cu SPE-amb , Zn SPE-amb , Co SPE-amb , and Ni SPE-amb were slightly elevated close to the mangrove forests, possibly as a result of inputs from the organic carbon-rich mangrove sediment pore waters (46). The NBC showed elevated concentrations of S SPE-amb , P SPE-amb , and Zn SPE-amb but lower concentrations of Fe compared to high-salinity estuarine samples (Fig.…”
Section: Elemental Composition Of Dom Spe-amb In the Amazon Plumesupporting
confidence: 71%
“…There was some evidence for an outer-estuary increase in P SPE-amb , Zn SPE-amb , and Ni SPE-amb at salinities between 15 and 30. Concentrations of S SPE-amb and P SPE-amb offshore from the mangrove forests were similar to those observed in the riverine endmember, while A 254SPE-amb , Cu SPE-amb , Zn SPE-amb , Co SPE-amb , and Ni SPE-amb were slightly elevated close to the mangrove forests, possibly as a result of inputs from the organic carbon-rich mangrove sediment pore waters (46). The NBC showed elevated concentrations of S SPE-amb , P SPE-amb , and Zn SPE-amb but lower concentrations of Fe compared to high-salinity estuarine samples (Fig.…”
Section: Elemental Composition Of Dom Spe-amb In the Amazon Plumesupporting
confidence: 71%
“…According to the classical redox sequence between Fe and Mn, the reduced form of Fe is more easily oxidized than Mn, resulting in the preferential precipitation of Fe (hydr)oxides (Lee et al., 2007). Previous studies have suggested that the concentration of Ba in groundwater is controlled by adsorption and desorption (Gong et al., 2020; Hanor & Chan, 1977; Mori et al., 2019), while being affected by the Fe and Mn cycles (Coffey et al., 1997; Paytan & Kastner, 1996; Sanders et al., 2012). In comparison to the Fe cycle, the Mn cycle has a more pronounced impact on the concentration of Ba, as the affinity of Ba for Mn (hydr)oxides is significantly greater than that for Fe (hydr)oxides by several orders of magnitude (Balistrieri & Murray, 1986; Charette et al., 2005; Charette & Sholkovitz, 2006; Mishra & Tiwary, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…1). The mangroves of the Coffs Creek estuary are dominated by Avicennia marina and cover an area of 0.2 km 2 (Mori et al 2019). The catchment geology is composed of late carboniferous basaltic bedrock in the upper reaches and quaternary sediment deposits on the coastal floodplain.…”
Section: Methodsmentioning
confidence: 99%